Algae in fish feed: performances and fatty acid metabolism in juvenile Atlantic Salmon - F Norambuena; K Hermon; V Skrzypczyk; JA Emery; Y Sharon; A Beard; GM Turchini (2015)
Algae are at the base of the aquatic food chain, producing the food resources that fish are adapted to consume. Previous studies have proven that the inclusion of small amounts (<10% of the diet) of algae in fish feed (aquafeed) resulted in positive effects in growth performance and feed utilisation efficiency. Marine algae have also been shown to possess functional activities, helping in the mediation of lipid metabolism, and therefore are increasingly studied in human and animal nutrition. The aim of this study was to assess the potentials of two commercially available algae derived products (dry algae meal), Verdemin (derived from Ulva ohnoi) and Rosamin (derived from diatom Entomoneis spp.) for their possible inclusion into diet of Atlantic Salmon (Salmo salar). Fish performances, feed efficiency, lipid metabolism and final product quality were assessed to investigated the potential of the two algae products (in isolation at two inclusion levels, 2.5% and 5%, or in combination), in experimental diets specifically formulated with low fish meal and fish oil content. The results indicate that inclusion of algae product Verdemin and Rosamin at level of 2.5 and 5.0% did not cause any major positive, nor negative, effect in Atlantic Salmon growth and feed efficiency. An increase in the omega-3 long-chain polyunsaturated fatty acid (n-3 LC-PUFA) content in whole body of fish fed 5% Rosamin was observed.